Carbon precipitation on metal nanostructures and diamond surfaces - RIENTONG, Komkrit; SUKSERM, Akkarach; SUNTORNWIPAT, Nattakarn; PINSOOK, Udomsilp (Journal of Metals, Materials and Minerals, 2026)
The interaction between diamond and a nickel (Ni) layer plays a crucial role in understanding the formation of graphene and its energy dynamics on metal-diamond substrates. In this study, we investigate the optimal positions of graphene relative to a catalyst layer on diamond by analyzing total energies obtained from self-consistent field (SCF) calculations using Quantum ESPRESSO. The structures of graphene, diamond (100), and the catalyst layers were constructed and simulated both individually and in combination. Energy comparisons between the combined structures and the sum of their individual components were conducted to identify favorable graphene positions. Our simulations show that graphene is stable both beneath and above the Ni layer, with energy differences of –0.04 Ry and –0.33 Ry, respectively, relative to the sum of the individual energies, indicating that graphene formation is more favorable above the Ni layer. Furthermore, an energy barrier analysis reveals that carbon atoms on the diamond surface can diffuse through the catalyst layer. These findings provide insights into graphene formation and carbon diffusion in the case of Ni as a catalyst, offering a foundation for further experimental and computational studies.